Project-Based Learning Design in Secondary Schools: Enhancing Students' Collaborative and Creative Skills - Naila Rohmaniyah; Siti Wulan Asih (Yayasan Azhar Amanaa Yogyakarta, 2024)
This study investigates the implementation of Project-Based Learning (PjBL) in secondary schools, focusing on its impact on enhancing students' collaborative and creative skills. The research employs a mixed-methods approach, including classroom observations, interviews with teachers and students, and analysis of student projects. Results indicate that PjBL fosters an active learning environment that significantly improves students’ ability to work collaboratively and think creatively. Students engaged in PjBL showed increased motivation and a deeper understanding of subject matter, demonstrating enhanced problem-solving and teamwork skills. However, the study also highlights several challenges, such as time constraints, limited resources, and difficulties in aligning PjBL with traditional curricula, which hinder its broader application. Teachers reported needing more professional development and support to effectively implement PjBL strategies. Despite these challenges, the positive outcomes suggest that PjBL is a promising pedagogical approach that can better prepare students for the demands of the 21st century. The findings underline the need for educational institutions to address the barriers to PjBL implementation and provide adequate training and resources to teachers. This study contributes to the growing body of literature advocating for innovative teaching methods that emphasize student-centered learning and the development of essential life skills.